Model UTAUT dalam Memprediksi Minat Penjual/Seller untuk Menggunakan TikTok Shop - Lina Affifatusholihah; Farah Putri Wenang Lusianingrum (Sains: Jurnal Manajemen dan Bisnis, 2023)
TikTok has launched an online shopping feature called TikTok Shop in Indonesia in April 2021. In October 2022, TikTok launched another online shopping feature called Shopping Center which allows users to make transactions more easily. This article presents the results of implementing the UTAUT model on seller intentions to use the TikTok Shop. The population in this study is the unknown number of sellers in the TikTok Shop. Therefore, the sampling technique uses non-probability sampling. The number of samples that were successfully collected and used were 230 respondents. We use the PLS-SEM analysis technique. The effect of performance expectations on behavioural intention is significant. The effect of business expectations is also positive and significant. Likewise, the influence of social influence on the seller's intention to use the TikTok Shop is relevant, and the effect of facilitating conditions is positive and significant.